1991
DOI: 10.1159/000112185
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Aspects of Gaucher Disease

Abstract: Gaucher disease is the most common sphingolipid storage disorder. Due to its high prevalence it may appear with a nonrelated neurological disease and be misinterpreted as Gaucher type 3. A family is described in which 2 Gaucher brothers presented different clinical signs. Molecular analysis has shown that both carried two mutated alleles. One allele had a G to C transversion at nucleotide 3119 of the active gene (Asp140-His) while the other presented two base pair changes, an A to C transversion at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
4
0

Year Published

1993
1993
1998
1998

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 9 publications
(10 reference statements)
1
4
0
Order By: Relevance
“…The 1448C mutation has been found in patients in all ethnic populations (Theophilus et al, 1989;Firon et al, 1990). Our results show that the frequency of the 1448C mutation in Japanese patients is similar to that of other ethnic groups (Levy et al, 1991). The phenotype-genotype relationships concerning this mutation are a little complex because of methods of mutation analysis, such as whether by screening for only this mutation site or by sequencing of entire coding region.…”
Section: Discussionsupporting
confidence: 54%
“…The 1448C mutation has been found in patients in all ethnic populations (Theophilus et al, 1989;Firon et al, 1990). Our results show that the frequency of the 1448C mutation in Japanese patients is similar to that of other ethnic groups (Levy et al, 1991). The phenotype-genotype relationships concerning this mutation are a little complex because of methods of mutation analysis, such as whether by screening for only this mutation site or by sequencing of entire coding region.…”
Section: Discussionsupporting
confidence: 54%
“…A homozygous T to C transition at glucocerebrosidase cDNA nucleotide position 1448, which results in L444P, is frequently found in Gaucher disease patients with neurological involvement. This mutation can result from either a single base substitution [Theophilus et al, 1989;Tsuji et al, 1987] or an unequal crossingover between the glucocerebrosidase functional gene and pseudogene creating a fusion gene or complex allele [Latham et al, 1990;Levy et al, 1991;Zimran et al, 1990]. It was postulated that a T to C single base substitution will result in type 3 Gaucher disease, whereas the complex allele will result in the type 2 form [Latham et al, 1990;Dahl et al, 1990].…”
mentioning
confidence: 99%
“…A T+C transition mutation at cDNA nucleotide 1448 (genomic nt 6433) that results in 444Le~+444Pro has frequently been found among patients with type 2 and type 3 Gaucher disease (3). This T6433C mutation may result from a single base substitution (3,4) or an uneven crossing-over between the functional gene and pseudogene of glucocerebrosidase that creates a "complex allele" (5)(6)(7). While the base substitution in the homozygous form was demonstrated to be the only mutation detected in patients with type 3 Gaucher disease in Sweden ( 8 ) , a number of type 2 Gaucher disease patients were found to be genetic compounds; i.e., they are heterozygous for this base substitution and the complex allele (5,6).…”
mentioning
confidence: 99%
“…This T6433C mutation may result from a single base substitution (3,4) or an uneven crossing-over between the functional gene and pseudogene of glucocerebrosidase that creates a "complex allele" (5)(6)(7). While the base substitution in the homozygous form was demonstrated to be the only mutation detected in patients with type 3 Gaucher disease in Sweden ( 8 ) , a number of type 2 Gaucher disease patients were found to be genetic compounds; i.e., they are heterozygous for this base substitution and the complex allele (5,6). It was also reported that the complex allele in the homozygous form is incompatible with life and results in spontaneous abortion during early fetal development (9).…”
mentioning
confidence: 99%